Interpretation of the Part of Tabarak, for Sheikh Abdul Qadir Maghrabi: A Critical Study - Alshyyab , Ahmad Hussein (Dirasat: Shari’a and Law Sciences, 2020)
This study dealt with the effort of Sheikh Abdul Qadir Al-Maghribi in his interpretation of Tabarak part looking at his method, and clarifying some of the observations, with the aim of revealing the extent to which he agrees or disagrees with the interpretations considered by the Sunnis, and revealing the ability to classify his interpretation within the interpretations that are similar to his interpretation. It is revealed that Sheikh Abdel Qader Al Maghribi is one of the followers of the mental school (the school of Sheikh Muhammad Abdo) and he tends to isolate in the methodology of rational thinking. In his interpretation, there were many observations related to his mental school, such as some isolationisms and interpretation. In his interpretation, Al-Maghribi relies heavily on language, and almost no verse is devoid of linguistic significance. Al-Maghribi is also considered one of the admirers of Western civilization, as this affected his interpretation as he exaggerated in citing modern scientific discoveries, to the extent of the cost that leads to the wrong inference. However, he is praised for his reformist tendency and fighting heresies, and his linguistic ability to formulate phrases in an easy and attractive manner.